Digital Transformation, Sustainability Strategy and Performance in Indonesian Energy Firms - Hermawan, Siti Nur Azizah Putri; Choiriah, Siti (Jurnal Sains Sosio Humaniora, 2026)
The growth of Indonesia’s manufacturing sector slowed from 5.33% (Q1 2023) to 4.62% (Q2 2023). In this condition, sustainability performance emerges as a crucial indicator reflecting the firm’s capability in maintain social and environmental responsibility while minimizing potential long-term risks. This research seeks to analyze the effect digital transformation and sustainability strategy affect sustainability performance, with sustainability commitment positioned as a moderating construct. The research population includes 83 firms within the sector registered on the IDX between 2020 and 2023. The sampling method used purposive sampling, resulting in 43 companies that met the criteria, with 172 observations over four years. The dataset was sourced obtained from annual and sustainability reports, and analyzed using Moderated Regression Analysis with panel data through EViews12 software. The findings show that both digital transformation and sustainability strategy exert a positive and empirically significant effect sustainability performance. Still, sustainability commitment does not serve as a moderating in the digital transformation–sustainability performance relationship, but it does moderate association between sustainability strategy and sustainability performance outcomes.